Superneutrality of Money under Open Market Operations - Stefan Homburg (Center for Economic Studies and ifo Institute (CESifo), 2015)
Monetary policy is superneutral in an overlapping generations model. Previous authors have argued that superneutrality does not hold in such a setting. However, the standard results rely on the counter-factual premise of helicopter money and are overturned if money creation through open market operations is taken into account. This result suggests that a more realistic representation of monetary policy may generally be helpful.
Keywords: E43; E52; H55; 330; superneutrality; open market operations; seigniorage; monetary policy; overlapping generations